Species composition and seasonal dynamics of lepidopterous stemborers on maize and the elephant grass, Pennisetum purpureum (Moench)(Poaceae), at two forest margin sites in Cameroon - Ndemah, R.; Schulthess, F.; Poehling, H.; Borgemeister, C. (2000)
Lepidopterous stem borers were monitored on plots of maize, Zea mays, and elephant grass, Pennisetum purpureum (Moench), during two consecutive cropping seasons and the off-season at two forest margin locations, Nkolbisson and Minkomeyos, in Cameroon. Busseola fusca (Fuller), Sesamia calamistis (Hampson) (Lepidoptera: Noctuidae) and Eldana saccharina Walker (Lepidoptera: Pyralidae) were found on both hosts. In addition, Cryptophlebia leucotreta (Meyrick) (Lepidoptera: Tortricidae) and Mussidia nigrivenella Ragonot (Lepidoptera: Pyralidae) were collected from maize, and Poeonoma serrata (Hampson) (Lepidoptera: Noctuidae) from elephant grass. Busseola fusca was the most abundant species on both host plants. The numbers of eggs per square metre on different plant hosts was not significantly different, whereas numbers of larvae and pupae were 3-9 times higher on elephant grass than on maize. Analysis of numbers of B. fusca larvae according to size/age classes indicate that all sizes tended to be more abundant on elephant grass than on maize, but significant differences were found only during the second season at Minkomeyos, when densities were high. No significant differences were found between host plants for diapausing larvae and pupae. The implications for the possible function of the grass as a trap plant or reservoir for natural enemies in the management of B. fusca are discussed.